The effect of nco-polyol on mechanical properties, morphology and water absorption of low density polyethlene / water hyacinth fiber (Eichhornia crassiper) composites - Supri, A. Ghani, Dr.; Lim, B. Y. (Universiti Kebangsaan Malaysia (UKM), 2011)
Organized by Universiti Kebangsaan Malaysia (UKM), 21st - 22nd October 2009 at Palm Garden Hotel, IOI Resort, Putrajaya, Malaysia.